Timeliness of financial reporting and audit committee effectiveness: evidence from UAE - Al-Muzaiqer, Mohammed Ali Hussein; Ahmad, Maslina; Abdul Hamid, Fatima (UNIMAS Publisher, 2018)
This study aims to examine the contemporary timeliness of financial reporting in the United Arab Emirates (UAE), and the impact of audit committee effectiveness on this timeliness. Timeliness of financial reporting in this study is measured by audit report lag (ARL), which is the number of days between the date of the financial year end and the date of the audit report. The data from listed companies on the UAE capital markets; Abu Dhabi Securities Exchange (ADX) and Dubai Financial Market (DFM), for three years from 2011 to 2013 resulted in 298 observations. The main statistical techniques of the study are means and multiple regressions. The findings show that generally all companies meet the submission deadlines imposed by the two UAE markets. Furthermore, ARL is influenced by audit committee size and profitability, while no evidence is found to support the effect of audit committee expertise, audit committee meetings and firm size on ARL.The results of the study show that only audit committee size has a significant influence in reducing ARL. This may be attributed to having minimal variation in the implementation of the Code of Corporate Governance (CCG), particularly audit committee attributes, in the UAE. The results suggest that the current governance by audit committees is adequate to ensure that the financial reports of companies in the UAE are timely. However, except for audit committee size, the other audit committee attributes are unable to further shorten ARL. The capital markets in the UAE and its CCG are relatively new. Hence, regulatory requirements may be less stringently implemented by companies in this country. Consequently, timely audited financial reports are demanded by local and international investors to make decisions and alleviate speculation. Thus, determining audit committee attributes that reduce ARL is beneficial to the UAE markets, the listed companies and investors.